Practical Protocol for Comprehensively Evaluating Sulfur-Fumigation of Baizhi Based on Metabolomics, Pharmacology, and Cytotoxicity - Deng, Ai-Ping; Kang, Chuan-Zhi; Kang, Li-Ping; Lyu, Chao-Geng; Zhang, Wen-Jin; Wang, Sheng; Wang, Hong-Yang; Nan, Tie-Gui; Zhou, Li; Huang, Lu-Qi; Zhan, Zhi-Lai; Guo, Lan-Ping (Frontiers in Pharmacology, 2022)
Sulfur Angelicae Dahuricae Radix (Baizhi) is a common medicinal herb in Asian countries. A practical protocol combining metabolomics, pharmacology, and cytotoxicity was developed to comprehensively evaluate the influence of sulfur-fumigation on the quality of Baizhi. Furocoumarins could be transformed into sulfur-containing compounds during the sulfuring process, among which 1 and 3 were purified with relatively high abundance and identified as 3,4-dihydrobyakangelicin-4-sulfonic acid and (4R,12S)-3,4-dihydrooxypeucedanin hydrate-4-sulfonic acid (OXH-S), respectively. OXH-S was found to be an addition product of sulfite and oxypeucedanin hydrate (OXH-N). Then, the cytotoxicity and anti-inflammatory activity of OXH-N, OXH-S, and water extracts of sulfured (extraction-S), and unsulfured Baizhi (extraction-N) were evaluated. OXH-S and extraction-S were less toxic than OXH-N and extraction-N, respectively. A comparison of OXH-N with OXH-S and extraction-N with extraction-S showed no significant differences in anti-inflammatory activity. These results suggest that sulfur fumigation can reduce toxicity and does not influence the anti-inflammatory activity of Baizhi, even after chemical composition changes. The proposed protocol based on marker screening, pharmacology, and safety evaluation provides a scientific basis for the standardization and regulation of sulfured Baizhi and other medical materials.